İslam hukukunda emanet akidlerinin tazmine konu olduğu durumlar (vedîa ve âriyet akidleri çerçevesinde) - Keleş, Elif (My University, 2022)
İnsanın, isteyerek veya istemeyerek diğer insanlara zarar vermesi mümkündür. Hukuk sistemleri tarafından insanların verdikleri zararın giderilmesi gayesi güdülmüştür. Bu amaçla Türk hukukunda “sorumluluk”, İslam hukukunda ise “damân” kavramı, üzerinde durulan önemli bir konu olmuştur. Hukuk sistemleri damânın/ sorumluluğun sebepleri ve unsurları gibi temel konularda düzenleme yapmayı önemsemişlerdir. Bu anlamda “akdî sorumluluk” veya İslam hukukunda “damânü’l-akd” olarak ifade edilen sebep önemli bir yere sahiptir. İslam hukukunda bu konu akidlerin tazmin bakımından ayrımına göre şekillenmiştir. Tazmin yükümlülüğü bakımından emanet akidleri, damân akidlerinden farklı olduğu için önem arz etmektedir. Emanet akitlerinde emanet malı teslim alan kişinin malın telefi halinde tazminle sorumlu olması için teaddî ve taksîr olarak ifade edilen davranışlarda bulunması gerekmektedir. Bu tez vedîa ve âriyet akdi bağlamında emanet akidlerinde akid konusu malın tazmin edilmesine sebep olan durumları konu edinmiştir. Çalışmada ilk olarak emanet akidlerinin tazmin açısından konumu belirlenmiştir. Bu amaçla damânın tanımı, sebepleri ve unsurları mukayeseli şekilde sunulmuştur. İkinci bölümde ise vedîa ve âriyet akidlerinde akid konusu malın tazmin edilme sebepleri detaylı olarak incelenmiştir.

People, by nature, interacts with other people in the society. This interaction is sometimes legal, such as a contract, sometimes it is illegal like usurpation and destruction. As a result of these relationships, it is possible for a person to damage other people’s own volition or involuntary. Therefore legal systems have aimed to repair the damage done by people. Because of this purpose, responsibility in Turkish law and damân in Islamic law have been an important issue. Legal systems have given importance to regulate fundamental issues such as the casues and conditions of responsibility/ damân. In Islamic law, this issue determines according to distinction of contracts in terms of compensation. In order for the person take delivery property to be responsible for compensation in the escrow contracts, she must act in ways that are expressed as teaddi and taksir. In terms of compensation obligation, escrow contracts are important because they are different from daman contracts. This thesis, deals with the situations that cause the compensation for the subject matter of the contract in the escrow contracts in the context of the bailment contract (vedîa) and loan agreement (âriyet). In the study, firstly, the position of escrow contracts in terms of compensation was determined. Because of this purpose, the definition of damân, the casues and conditions responsibility are presented in a comparative manner. In the second chapter, the reasons for the compensation for the property subject to the contract in vedia and ariyat contracts are examined in detail.
Keywords: Akid; Âriyet Responsibility; Compansation; Contract; Damân; Emanet; Islamic law; İslam hukuku; Sorumluluk; Trust; Vedîa